Tailoring Catalytic Properties of Copper Manganese Oxide Nanoparticles (Hopcalites-2G) via Flame Spray Pyrolysis - Wegner, Karl; Medicus, Maximilian; Schade, Elke; Grothe, Julia; Kaskel, Stefan (ChemCatChem, 2018)
Humidity tolerant copper manganese oxide catalysts of the second generation (“Hopcalites-2G”) were produced by flame spray pyrolysis process (FSP) and their catalytic activity for carbon monoxide oxidation under dry and humid conditions was evaluated. The effects of synthesis parameters such as flame specific variables (OFR=oxygen to fuel ratio, sheath gas, reactor) and the precursor specifications (composition, concentration, solvent) were investigated systematically. From the findings of the synthesis variations, it was possible to identify key factors decisive to achieve a high catalytic activity for CO oxidation under humid conditions. The most important characteristics are phase composition, specific surface area and the carbon content to achieve increased long-term stability of the flame made catalysts under humid conditions. A high productivity in the flame-based Hopcalite synthesis was achieved with catalysts performances similar or better than that of the commercial Hopcalite catalyst Carulite 300 (CARUS). The most active catalyst showed 50 % higher CO conversion after one hour on stream at 50 °C and humid conditions compared with the reference. The latter is a crucial step towards an improved humidity tolerance of Hopcalite catalysts in respiratory filter applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: CO oxidation; flame spray pyrolysis; Hopcalite; humidity tolerance; respiratory filter